Równość i solidarność w niespokojnych czasach : reformy państwa dobrobytu w okresie światowego kryzysu finansowego i gospodarczego - Mering, Tomasz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article presents the concept of the welfare state and shows the impact of the recent financial and economic crisis on the scope of the social rights in the Member States of the European Union. The study finds that since the 80s of the last century, welfare states have come under pressure, the effect of which has been to carry out reforms aimed towards limiting the level of social protection of employees and reducing social spending. The reforms have accelerated in times of economic recession, especially in countries that are members of the euro area, which had to meet the requirements related to reducing budget deficits and public debt. The article points to the growing importance of external factors to the development trajectory of welfare states and draws attention to the role of public discourse in formulating anti-crisis programs
Keywords: solidarność społeczna; równość; kryzys finansowy; państwo dobrobytu